Using MCDA-C to assess the organizational performance of industries operating at Brazilian maritime port terminals - André Andrade Longaray; Leonardo Ensslin; Ademar Dutra; Sandra Rolim Ensslin; Ricardo Brasil; Paulo Munhoz (Operations Research Perspectives, 2019)
This article describes the use of the constructivist multicriteria decision aid (MCDA-C) model as an intervention instrument, using a case study of a fertilizer industry located at a Brazilian maritime port terminal, with the goal of developing a customized performance evaluation model to help its management process. The sequence of steps created to develop the model occurred interactively through interviews with the decision maker. The developed model allowed the decision maker to incorporate the unique aspects of the company and environment, thereby widening the performance evaluation possibilities and enhancing organizational management.
Keywords: 330; Multicriteria methods; Performance evaluation; MCDA-C; Maritime port terminals; Soft operations research; MACBETH